2000
DOI: 10.1115/1.1287589
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Dynamic Normal Characteristics of Machined Joint Surfaces

Abstract: This paper presents an experimental investigation on the normal dynamic characteristics of several machined joint surfaces, i.e., the varying principle of the normal dynamic stiffness and damping with exciting frequency, relative displacement and static pre-load under different joint conditions, including joint materials, mediums, machining methods and surface roughness, etc.. The joint parameters are extracted from experimental data by establishing the theoretical model of the joint surfaces, and the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 5 publications
2
30
0
Order By: Relevance
“…The results from Connolly and Thornly [19] showed that the normal stiffness is mainly influenced by the machined texture of rough surfaces and little by their hardness. Fu et al [21] presented an experimental investigation of normal parameters of several machined rough surfaces and found that the normal stiffness increases with increasing normal load. Fu et al [21] presented an experimental investigation of normal parameters of several machined rough surfaces and found that the normal stiffness increases with increasing normal load.…”
Section: Introductionmentioning
confidence: 99%
“…The results from Connolly and Thornly [19] showed that the normal stiffness is mainly influenced by the machined texture of rough surfaces and little by their hardness. Fu et al [21] presented an experimental investigation of normal parameters of several machined rough surfaces and found that the normal stiffness increases with increasing normal load. Fu et al [21] presented an experimental investigation of normal parameters of several machined rough surfaces and found that the normal stiffness increases with increasing normal load.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, D. J. Whitehouse and J. F. Archard studied the relationship between peak height of the contact surface micro-protrusions among the mechanical bonding surfaces and the curvature of the peak. Moreover, the joint distribution density was studied and WA model was proposed (Blossey, 2003;Hoffmann and Gaul, 2003). According to the GW and WA models, R. A. Oninn and J. F. Archard used WA to determine the separation relationship between contact area, load and surface, and the calculation results are consistent with GW, which is called OA model (Jackson, 2006;Fu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A. Greenwood and J. B. P. P. Williamson used Gaussian distribution method to simulate the distribution law of micro-convex among the joint surface, and proposed a GW model based on single hypothesis (Greenwood and Williamson, 1996). However, since the premise assumptions in this model were independent mutually, they could only be applied under conditions of small load.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the contact problem between the rough surfaces is nonlinear and complicated, the joint surface contact damping parameters usually got by the method of experiment to identify, in the former studies. [3][4], with the development of fractal contact theory application in rough surface [5], researchers began to expand the research field of fractal contact model in the field of bolt joint dynamic characteristic. References [6][7][8] researched the joint surface contact stiffness contact damping based on two-dimensional fractal surface, and the corresponding fractal model is established.…”
Section: Introductionmentioning
confidence: 99%